ACCOUNTING SYSTEM AND FINANCIAL MANAGEMENT ACCOUNTABILITY VILLAGE OWNED ENTERPRISES (BUMDes)“MITRA KARYA SEJAHTERA”TOAPAYA SELATAN VILLAGE BINTAN DISTRICT - Reza Chandra; Puji Lestari; Hairul; Syafrizal; Yani Endang Irmarita; Heri Purwandi; Indrayani; Muammar Khaddafi; Jumadil Saputra (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Village Owned Enterprises Mitra Karya Sejahtera South Toapaya Village, Bintan Regency in terms of accounting system practices are still very simple and cannot present proper financial reporting so that financial accountability is still considered very weak. This study was obtained through interviews with administrators responsible for managing financial statements. The collected data is reduced and reanalyzed for conclusions The results show that 1) Bumdes' financial management uses a simple bookkeeping system and does not yet reflect systematic financial reporting, 2) Financial statements have not been accountable and present appropriate information 3) the financial information of Bumdes is not in accordance with the principles of accountability, 4) The level of knowledge of financial managers on accounting is still lacking causing inaccuracies in financial statements. Based on this research, it is hoped that it can be a means of evaluation for BUMDes Village-Owned Enterprises Mitra Karya Sejahtera, besides that it can be used as material for scientific studies to add insight into the accountability of financial statement management in BUMDes.